PERSEPSI KELUARGA TENTANG DUKUNGAN PERAWAT CRITICAL CARE DI RUANG INTENSIVE RSUD ARIFIN ACHMAD PROVINSI RIAU - Hutapea, Yosepin Jelita (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Intensive care unit is hospital care that has the goal of treating patients with life-threatening conditions due to disease, trauma, or surgery. The purpose of this research is to determine family perceptions about the support of critical care nurses in the intensive care unit at RSUD Arifin Achmad Pekanbaru. The design is Quantitative research with descriptive research design. The sampling technique in this study was accidental sampling technique. The measuring tool used is a family perception questionnaire about nurse support. The analysis used is the analysis of frequency distribution data. The results of this study indicate family perceptions about critical care nurse support from 45 respondents, namely sufficient perceptions (60%), perceptions based on relationships with patients obtained sufficient perceptions (52,4%) and perceptions based on recent education also showed sufficient perceptions (58,3%). Overal it was concluded that the perceptions held by the patient's family in this study were in the sufficient category, the family viewed and assessed treatment in the intensive care unit not in accordance with the needs, expectations and desired circumstances. The result can be used as basic data, information, evidence based to carry out further research and it is hoped that the hospital will provide religious leaders and spiritual support to help families in facing critical conditions.